2012
DOI: 10.1080/10852352.2012.707439
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Social Consequences of Adverse Childhood Experiences (ACE) Across the Lifespan: An Introduction to Prevention and Intervention in the Community

Abstract: This introduction to the themed issue overviews of the Adverse Childhood Experiences (ACE) Study and discusses prevention and intervention with ACE and their consequences in communities. A commentary by Dr. Robert Anda, an ACE Study Co-Principal Investigator, is incorporated within this introduction. Implications of articles within the issue are addressed, and next steps are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(96 citation statements)
references
References 7 publications
4
84
0
8
Order By: Relevance
“…However, there were no differences in total scores with respect to relationship status; being a non-native English speaker, full-or parttime student, or first-generation college student; working while in school; or receiving student loans. The lack of significant relationships between ACE scores and any of these variables was somewhat surprising, given previous findings suggesting a relationship between ACE scores, educational and employment attainment, and socioeconomic status (Davidson, 2010;Larkin et al, 2012; Esaki and Larkin (2013). Mersky, Topitzes, & Reynolds, 2013;Nurius et al, 2015).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, there were no differences in total scores with respect to relationship status; being a non-native English speaker, full-or parttime student, or first-generation college student; working while in school; or receiving student loans. The lack of significant relationships between ACE scores and any of these variables was somewhat surprising, given previous findings suggesting a relationship between ACE scores, educational and employment attainment, and socioeconomic status (Davidson, 2010;Larkin et al, 2012; Esaki and Larkin (2013). Mersky, Topitzes, & Reynolds, 2013;Nurius et al, 2015).…”
Section: Discussionmentioning
confidence: 75%
“…The prevalence of ACEs has been labeled a "chronic public health disaster" (Anda & Brown, 2010;Larkin, Shields, & Anda, 2012) and a "hidden crisis" (Center for Youth Wellness, 2013). Yet effects of these adverse experiences often don't emerge until much later in life and therefore typically are not associated with the original traumas.…”
Section: Adverse Childhood Experiences Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial adversity – defined as life-influencing events that result in significant stress (Psychology Dictionary, 2014) – is prevalent and has a negative impact on health (Felitti et al, 1998; Larkin, Shields, & Anda, 2012; Shonkoff & Garner, 2012). For example, the Adverse Childhood Experiences (ACE) studies found that two-thirds of middle class adults had experienced some form of childhood adversity (e.g., exposure to domestic violence (DV)), and that these adversities were significantly associated with the leading causes of adult morbidity and mortality (Felitti et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals face a higher risk of suffering from substance use disorders, depression, and trauma and stressor-related disorders, including post-traumatic stress disorder (PTSD). Unresolved trauma is linked to poor academic achievement, early sexual activity, financial stress, poor work performance, heart disease, and liver disease (Anda et al, 2014;Larkin, Shields, & Anda, 2012).…”
mentioning
confidence: 99%